Experimental study of relative permittivity of atmospheric ice - Bhattu, Shravan K; Mughal, Umair Najeeb; Virk, Muhammad Shakeel (2013)
Link to publishers version: https://www.ijee.ieefoundation.org/vol4/issue3/IJEE_02_v4n3.pdf Open Access under the terms of the Creative Commons CC BY licence. Atmospheric icing on onshore and offshore structures is problematic, if we don’t detect and remove it. Despite of various ice detection techniques, capacitor based ice sensing technique is interesting one, as it is based on dielectric properties of material. This technique of measuring icing event is simple and cost- effective. Based on the dielectric concept, an experi mental setup comprised of two rectangular aluminum bars in parallel connected with an LCR meter, th ermocouples, data acquisition system and computer was designed at the cold room chamber facility of Narvik University College to study the transient response of dielectric constant of ice at different opera ting atmospheric conditions. Analysis showed that depending on the atmospheric ice type the capacita nce varies due to the variation in temperature.